Implementation of Good School Governance (GSG) at Islamic Primary School Darud Dakwah Wal Irsyad (DDI) North Sangatta, East Kutai Regency, East Kalimantan - Hardianti, Hardianti; I.R Sari, Wulan; Lahjie, Annisa Abubakar (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This research aims to analyze the implementation of Good School Governance (GSG) at SD Islam DDI Sangatta Utara in Kutai Timur Regency, East Kalimantan, and its relation to school performance and accreditation achievement. The implementation of GSG focuses on four main principles namely accountability, transparency, participation, and equity, which contribute to strengthening school governance. This study employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving the principal, teachers, school committee members, and parents as informants. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that the implementation of Good School Governance at SD Islam DDI Sangatta Utara has been initiated but remains suboptimal. Accountability is implemented through reporting of school programs, the documentation has not fully served as a public accountability instrument. Transparency is still limited and has not reached all stakeholders effectively. Community participation exists but mostly focuses on basic support and occasional school activities rather than active involvement in program planning and evaluation. Equity in educational services is ensured in terms of students’ treatment and learning opportunities. However, it is not fully supported by adequate educational facilities and infrastructure. School performance remains in the fair category, as reflected by the continued accreditation score of C, with infrastructure issues as the primary factor hindering quality improvement. The study concludes that the principles of GSG play a strategic role in enhancing the quality of education at SD Islam DDI Sangatta Utara. Therefore, strengthening each principle of GSG and improving collaboration among stakeholders are needed to support the improvement of school performance and sustainable accreditation development